(untitled) (PJDOL, 2023)
This article is a literary review regarding emerging trends of distance education in the world with a particular focus on Pakistan. Many countries of the developed world have already started distance and online education. This micro level meta-analysis of distance education has found that for higher education, students somehow like the use of internet technology for getting in touch with peers and teachers. R